Gamified Assessment as a Catalyst for Skill Mastery in Online ESP Learning: An LMS-Based Investigation - Dewi Hidayati (Nexus Publishing NXP, 2025)
Despite the growing adoption of gamification in online English for Specific Purposes instruction, existing scholarship remains fragmented, often privileging learner motivation or engagement while underexamining how gamified assessment functions as a mechanism for measurable skill mastery within learning management system–mediated environments. Addressing this gap, the present study aims to investigate the role of gamified assessment in fostering skill-specific achievement in online ESP learning. Employing a sequential explanatory mixed-methods design, the study was conducted in an anonymous private higher education institution in East Java, Indonesia. Quantitative data were obtained from pre- and post-assessment scores embedded in LMS-based gamified tasks completed by 56 undergraduate ESP learners enrolled in a discipline-specific course, while qualitative insights were generated through a structured questionnaire and follow-up interviews with six purposively selected participants. The findings indicate that gamified assessment supported sustained learner engagement, clearer performance benchmarking, and incremental improvement in targeted ESP skills, particularly in task-based language use aligned with professional contexts. However, the results also reveal challenges related to uneven digital literacy, assessment fatigue, and the risk of overemphasizing game mechanics at the expense of reflective learning. These findings underscore the need for pedagogically balanced gamified assessment designs that prioritize validity, skill alignment, and contextual sensitivity in online ESP settings.